Neighborhood socioeconomic status and length of stay after congenital heart disease surgery - Vashist, Sudhir; Dudeck, Brandon S.; Sherfy, Beth; Rosenthal, Geoffrey L.; Chaves, Alicia H. (Frontiers in Pediatrics, 2023)
Background: Socioeconomic factors are associated with health outcomes and can affect post-operative length of stay after congenital heart disease surgery. The hypothesis of this study is that neighborhood socioeconomic status (SES) and race influence hospital stay after congenital heart disease (CHD) surgery. Methods: Pre- and post-operative data were collected on patients who underwent a benchmark CHD surgery at the University of Maryland Medical Center between 2011 and 2019. A neighborhood SES score was calculated for each patient using data from the United States Census Bureau and patients were grouped by high vs low SES neighborhoods. The difference of patient length of stay (LOS) from the Society for Thoracic Surgeons median LOS for that surgery was the primary outcome measure. Linear regression was performed to examine the association between difference from median LOS and SES, as well as other third variables. Results: Difference from median LOS was –4.8 vs –2.2 days in high vs low SES groups (p=0.003). SES category was a significant predictor of LOS in unadjusted and adjusted regression analyses. There was a significant interaction between Norwood operation and SES – patients with low neighborhood SES who underwent Norwood operation stay longer, but there was no difference in LOS by SES in patients who underwent other operations. Conclusions: Neighborhood SES is a significant predictor of LOS after congenital heart disease surgery. This effect was seen primarily in patients undergoing Norwood operation.